A method for preparing non-metal-doped silicon-based negative electrode material

By uniformly deposition of non-metal doping and silane on the porous carbon substrate, and multi-layer carbon coating and heat treatment, the problem of uneven distribution of doping elements is solved, and the performance of silicon-based anode material is significantly improved.

CN119750588AActive Publication Date: 2025-04-04SHENZHEN SOLID ADVANCED MATERIALS TECH CO LTD

Patent Information

Application Number
CN202510246762.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-04
Publication Date
2025-04-04
Estimated Expiration
2045-03-04

AI Technical Summary

Technical Problem

In the prior art, the distribution of non-metal doped elements in the silicon-based negative electrode material is uneven, resulting in poor material performance.

Method used

By preparing a porous carbon substrate with a hierarchical pore structure, and depositing non-metal doped gas and silane gas thereon in sequence, followed by multi-layer carbon coating and heat treatment, a uniformly doped silicon-based anode material was obtained.

Benefits of technology

The uniform distribution of non-metal doped elements in the silicon-based negative electrode material is achieved, and the cyclic stability, electrochemical properties and energy density of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750588A_ABST
    Figure CN119750588A_ABST
Patent Text Reader

Abstract

The present invention proposes a method for preparing a non-metal-doped silicon-based negative electrode material, comprising the following steps: preparing a porous carbon substrate with a hierarchical pore structure; sequentially depositing a non-metal-doped gas and a silane gas in the porous carbon substrate to obtain a non-metal-doped silicon-based material; performing a multi-layer carbon coating on the surface of the silicon-based material to obtain a silicon-based negative electrode precursor; and heat-treating the silicon-based negative electrode precursor to obtain a non-metal-doped silicon-based negative electrode material. The phenomenon of uneven doping is avoided, and the electrochemical performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for preparing a non-metal-doped silicon-based negative electrode material. Background Art

[0002] In recent years, silicon-based anodes have gradually become a strong competitor for the next generation of lithium-ion battery anode materials due to their ultra-high theoretical specific capacity (about 4200 mAh / g). Compared with traditional graphite anodes, silicon-based anodes can significantly improve the overall energy density of the battery. However, silicon undergoes large volume expansion and contraction (up to 300%) during the process of lithium ion insertion and extraction during charging and discharging, which can lead to damage to the electrode structure, resulting in poor cycle stability, rapid capacity decay and other problems. At the same time, another major difficulty in practical application is that the electronic conductivity of pure silicon anode itself is poor (1.56×10 -3 s / m), it must be compounded with carbon materials (such as graphite, carbon nanotubes, etc.) or doped with other elements before it can be used.

[0003] In the silicon-carbon negative electrode, the porous carbon substrate has a large number of defects, which affect the distribution of silane decomposed into amorphous silicon on it. Non-metallic doping can change the crystal structure of the porous carbon substrate and silicon, help alleviate the volume expansion of silicon during lithium insertion and extraction, and reduce the risk of pulverization and failure of silicon electrodes. However, most of the current doping methods remain in the small-scale experimental stage used in laboratories such as the sol-gel method and thermal reduction method, and are prone to problems such as uneven distribution of doping elements on the substrate and poor performance of the negative electrode material after doping. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a non-metallic doped silicon-based negative electrode material, aiming to solve the problem of uneven distribution of doping elements, which leads to poor performance of the negative electrode material.

[0005] To solve the above technical problems, the present invention is implemented as follows: the present invention provides a method for preparing a non-metal-doped silicon-based negative electrode material, comprising the following steps: S1. Preparing a porous carbon substrate with a hierarchical pore structure, wherein the pore size of the porous carbon substrate is 0.1-100 nm, and the hierarchical pore structure includes 30-90% micropores, 5-55% mesopores and 5-55% macropores in percentage, the pore size of the micropores is 0.1-2 nm, the pore size of the mesopores is 2-50 nm, and the pore size of the macropores is 50-100 nm; S2, sequentially depositing a non-metallic doping gas and a silane gas in the porous carbon substrate to obtain a non-metallic doped silicon-based material, wherein the non-metallic doping gas comprises a borane gas or a phosphine gas; S3, performing multi-layer carbon coating on the surface of the silicon-based material to obtain a silicon-based negative electrode precursor; S4. Heat-treating the silicon-based negative electrode precursor to obtain a non-metal-doped silicon-based negative electrode material.

[0006] In some embodiments of the present invention, step S1 comprises: S1.1. Clean, dry and crush the carbon source material to obtain a uniform particle size distribution, and the particle size D50 value is controlled at 5 to 10 μm; S1.2, adding a template material to the carbon source material, the mass ratio of the carbon source material to the template material is controlled at 1:2, heating to 800-1000°C, a heating rate of 5-10°C / min, and a holding time of 2-4h to obtain a premix; S1.3, transferring the premix to a hydrofluoric acid solution to remove the template material, controlling the temperature at room temperature, and reacting for 4 to 6 hours to obtain a porous carbon substrate with a hierarchical pore structure.

[0007] In some embodiments of the present invention, in step S1, the carbon source material includes at least one of porous carbon, natural graphite, artificial graphite mesophase carbon microbeads, and expanded graphite; The pore size of the porous carbon substrate is 0.1-100 nm, wherein, calculated by percentage, the hierarchical pore structure includes 30-90% of micropores, 5-55% of mesopores and 5-55% of macropores.

[0008] In some embodiments of the present invention, after step S1.3, step S1 further includes: S1.4, immersing the porous carbon substrate in potassium hydroxide or phosphoric acid solution, the proportion of which is controlled to be 2-10% of the mass of the carbon source, immersing for 1-4 hours, and calcining at 500-700° C. for 2-4 hours; S1.5, transferring the porous carbon substrate to a strong oxidant solution, controlling the temperature at 60-100°C, and reacting for 2-6 hours; S1.6. Use deionized water to wash repeatedly to remove unreacted products. The drying temperature is 100-150°C for 4-6 hours to obtain a porous carbon substrate with a hierarchical pore structure after activation.

[0009] In some embodiments of the present invention, step S2 includes: S2.1, placing the porous carbon substrate in a plasma vapor deposition reactor under an inert atmosphere, with an inert gas flow rate of 1-20 L / min, preheating to 400-700°C, and maintaining for 40-100 min to remove impurities and moisture adsorbed on the surface; S2.2, stop introducing the inert gas, introduce the non-metallic doping gas, the flow rate of the non-metallic doping gas is controlled at 0.5-10 L / min, the reaction temperature is 400-600°C, the plasma power is 200-500 W, and the doping time is 30-420 min; S2.3, stop introducing non-metallic doping gas, introduce silane gas, the silane gas flow rate is controlled at 0.5-10L / min, the reaction temperature is 500-700°C, the plasma power is 200-500W, and the doping time is 100-1500min; S2.4. Stop introducing silane gas, introduce an inert atmosphere, slowly lower the temperature to room temperature, and control the cooling rate at 5 to 20°C / min to obtain a non-metal-doped silicon-based material.

[0010] In some embodiments of the present invention, in step S2, The inert gas includes at least one of nitrogen, argon and hydrogen; The borane gas includes at least one of diborane, methylborane, tetraborane, pentaborane, decaborane, hexaborane and trimethylborane; The phosphine gas includes at least one of phosphine, diphosphine and triphosphine; The silane gas includes at least one of monosilane, disilane, and silane derivatives.

[0011] In some embodiments of the present invention, step S3 includes: S3.1, introducing a mixed gas of acetylene and hydrogen into a plasma vapor deposition reactor to perform a first deposition reaction, wherein the gas flow rate of acetylene is 5-10 L / min, the gas flow rate of hydrogen is 10-20 L / min, the reaction temperature is 500-800° C., the deposition time is 30-120 min, and the plasma power is 300-600 W to form a first carbon coating layer on the silicon-based material; S3.2. Stop introducing the mixed gas of acetylene and hydrogen, and introduce a mixed gas of ethylene or methane gas and nitrogen or argon gas to carry out a second deposition reaction. The gas flow rate of ethylene or methane is 2~6L / min, the gas flow rate of nitrogen or argon is 8~12L / min, the reaction temperature is 700~900℃, the deposition time is 20~80min, and the plasma power is 300~600W. The second carbon coating layer is formed on the first carbon coating layer to obtain a silicon-based negative electrode precursor.

[0012] In some embodiments of the present invention, the thickness of the first carbon coating layer is 5-15 nm, and the thickness of the second carbon coating layer is 3-10 nm; By volume ratio, acetylene: hydrogen = 1:2, ethylene or methane: nitrogen or argon = 1:3.

[0013] In some embodiments of the present invention, step S4 includes: S4.1, setting the heating rate to 5-10°C / min, until the temperature of the silicon-based negative electrode precursor reaches 800-1000°C, and the holding time is 120-240min; S4.2. Introduce ammonia or nitrogen gas with a gas flow rate of 5 to 15 L / min, adjust the heating rate to 2 to 5°C / min, until the temperature of the silicon-based negative electrode precursor reaches 1000 to 1200°C, and keep warm for 120 to 240 minutes to obtain a non-metal-doped silicon-based negative electrode material.

[0014] Compared with the prior art, the method for preparing a non-metal-doped silicon-based negative electrode material in the present invention has the following beneficial effects: In step S1, a porous carbon substrate with a hierarchical pore structure is prepared to provide pores of different scales (micropores, mesopores, macropores), providing an ideal substrate for uniform penetration and distribution of doping gas. This structure ensures that the doping gas can be evenly distributed throughout the volume of the material, thereby avoiding the situation in which the doping elements are limited to the surface or certain local areas in the traditional method.

[0015] In step S2, non-metallic doping gases such as borane or phosphine are introduced by vapor deposition technology. This method can ensure that the doping elements are uniformly infiltrated and react with the porous carbon substrate in a short time. Compared with traditional doping methods, this method can ensure that the doping elements are uniformly distributed in the material and avoid the problem of insufficient local doping.

[0016] The multi-layer carbon coating in step S3 enhances the structural stability of the material and ensures the bonding between the doping elements and the silicon substrate. The carbon coating not only prevents the expansion and rupture of the silicon particles, but also improves the conductivity of the material by providing additional conductive paths, while enhancing the uniformity and stability of the doping elements throughout the material.

[0017] The heat treatment process in step S4 promotes the chemical bonding between the doping elements and the silicon-based material, ensuring the uniformity and stability of the doping process. By precisely controlling the temperature, time and atmosphere of the heat treatment, the doping elements can penetrate deeper into the silicon-based material, avoiding uneven doping and further improving the electrochemical properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic flow chart of a method for preparing a non-metal-doped silicon-based negative electrode material in one embodiment of the present invention; Figure 2 is a scanning electron microscope image of the boron-doped silicon-based negative electrode material prepared by the present invention; Figure 3 It is a scanning electron microscope image of the phosphorus-doped silicon-based negative electrode material prepared by the present invention. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0020] Please refer to Figure 1 The present invention provides a method for preparing a non-metal-doped silicon-based negative electrode material, comprising the following steps: S1. Prepare a porous carbon substrate with a hierarchical pore structure.

[0021] Specifically, step S1 includes: S1.1. The carbon source material is cleaned, dried and crushed to obtain a uniform particle size distribution, and the particle size D50 value is controlled at 5 to 10 μm.

[0022] S1.2, adding template material to the carbon source material, the mass ratio of carbon source material to template material is controlled at 1:2, heating to 800-1000°C, heating rate of 5-10°C / min, holding time of 2-4h, to obtain a premix; S1.3. Transfer the premix to a hydrofluoric acid solution to remove the template material. The temperature is controlled at room temperature. The reaction time is 4 to 6 hours to obtain a porous carbon substrate with a hierarchical pore structure.

[0023] Through the operations of steps S1.1 to S1.3, the prepared hierarchical pore structure effectively increases the specific surface area and pore volume, which helps to improve the electrolyte permeability and lithium ion transmission rate of the electrode material.

[0024] In step S1.2, a predetermined pore structure is formed by adding a template material and carbonizing it at high temperature. Subsequently, in step S1.3, hydrofluoric acid is used to remove the template to ensure the uniformity and controllability of the pore structure and avoid collapse or irregular distribution of the pores. The template material is effectively removed by hydrofluoric acid treatment to ensure the purity and structural stability of the pores inside the porous carbon substrate, providing a good substrate for subsequent non-metallic doping and silicon deposition, and improving the cycle stability and electrochemical performance of the final negative electrode material. In step S1.1, a uniform carbon source material with a particle size D50 value controlled at 5 to 10 μm is obtained through cleaning, drying and crushing processes. Uniform particle size distribution helps to improve the overall uniformity of the porous carbon substrate and avoid structural defects caused by different pore sizes in subsequent processes.

[0025] After step S1.3, step S1 further includes: S1.4. Immerse the porous carbon substrate in potassium hydroxide or phosphoric acid solution, with the ratio controlled at 2-10% of the mass of the carbon source. After immersion for 1-4 hours, calcine at 500-700°C for 2-4 hours.

[0026] Chemical activation is performed by immersing the porous carbon substrate in potassium hydroxide or phosphoric acid solution and calcining it at 500-700°C. This process can effectively etch the carbon substrate, increase the number and volume of micropores and mesopores, further optimize the hierarchical pore structure, and increase the specific surface area. Chemical activation treatment can introduce more conductive paths, improve the overall conductivity of the porous carbon substrate, and at the same time, by increasing the complexity of the pore structure, enhance the mechanical stability of the material, and reduce the structural damage of silicon during the charge and discharge process.

[0027] S1.5. Transfer the porous carbon substrate to a strong oxidant solution, control the temperature at 60-100°C, and react for 2-6 hours.

[0028] Transferring the porous carbon substrate to a strong oxidant solution for treatment can introduce oxygen-containing functional groups such as carboxyl and hydroxyl groups on the carbon surface. These functional groups not only increase the hydrophilicity and chemical activity of the carbon substrate, which helps with subsequent non-metallic doping and silicon deposition, but also enhance the bonding force between the carbon layer and silicon particles, improving the structural stability and electrochemical performance of the material. Surface functionalization treatment enhances the ability to embed and de-embed lithium ions by introducing more active sites, thereby improving the capacity and cycle stability of the negative electrode material.

[0029] S1.6. Use deionized water to wash repeatedly to remove unreacted products. The drying temperature is 100-150°C for 4-6 hours to obtain a porous carbon substrate with a hierarchical pore structure after activation.

[0030] By repeatedly washing with deionized water, the residual chemical reagents and by-products from the chemical activation and strong oxidant treatment processes are removed to ensure the purity of the porous carbon substrate. This process effectively prevents impurities from interfering with the subsequent non-metallic doping and silicon deposition steps, and improves the electrochemical performance and stability of the final negative electrode material. The drying step ensures that the material is completely dry to prevent residual moisture from affecting subsequent processes and material properties. At the same time, by optimizing the washing and drying conditions, the pore structure of the porous carbon substrate is further stabilized to ensure that it maintains good morphology and performance during the subsequent preparation process.

[0031] In step S1, the carbon source material includes at least one of porous carbon, natural graphite, artificial graphite mesophase carbon microspheres, and expanded graphite; the pore size of the porous carbon substrate is 0.1-100 nm, wherein, calculated by percentage, the hierarchical pore structure includes 30-90% micropores, 5-55% mesopores, and 5-55% macropores. The pore size of the micropores is 0.1-2 nm, the pore size of the mesopores is 2-50 nm, and the pore size of the macropores is 50-100 nm.

[0032] By selecting porous carbon, natural graphite, artificial graphite mesophase carbon microspheres or expanded graphite as carbon source materials, the microstructure and performance characteristics of the porous carbon substrate can be flexibly adjusted to meet the needs of different application scenarios for negative electrode materials. The specified pore size is 0.1~100nm, and the proportion of micropores is 30~90%, mesopores 5~55%, and macropores 5~55%, ensuring that the porous carbon substrate has a high specific surface area and a multi-level pore structure. This pore distribution not only provides sufficient lithium ion storage sites, but also effectively buffers the volume change of silicon during charging and discharging, improving cycle stability.

[0033] The porous carbon substrate with hierarchical pore structure can significantly improve the permeability of the electrolyte and the transmission rate of lithium ions, reduce the ion diffusion resistance, and improve the rate performance and charge and discharge efficiency of the electrode material.

[0034] The multi-level pore structure provides additional buffer space, which can effectively absorb the volume expansion and contraction of silicon particles during the charging and discharging process, reduce the damage to the material structure, and extend the cycle life of the battery.

[0035] By controlling the selection of different carbon source materials and process parameters, the pore size distribution of the porous carbon substrate can be adjusted to meet the specific performance requirements of negative electrode materials for different battery applications, such as high energy density, high power density or long cycle life.

[0036] S2. Depositing non-metallic doping gas and silane gas in sequence in the porous carbon substrate to obtain a non-metallic doped silicon-based material, wherein the non-metallic doping gas includes borane gas or phosphine gas.

[0037] Step S2 includes: S2.1. Place the porous carbon substrate in a plasma vapor deposition reactor under an inert atmosphere with an inert gas flow rate of 1-20 L / min, preheat to 400-700°C, and maintain for 40-100 min to remove impurities and moisture adsorbed on the surface; the inert gas includes at least one of nitrogen, argon, and hydrogen.

[0038] S2.2. Stop introducing inert gas and introduce non-metallic doping gas, the flow rate of non-metallic doping gas is controlled at 0.5-10 L / min, the reaction temperature is 400-600°C, the plasma power is 200-500 W, and the doping time is 30-420 min; the borane gas includes at least one of diborane, methyl borane, tetraborane, pentaborane, decaborane, hexaborane, and trimethylborane; the phosphine gas includes at least one of phosphine, diphosphine, and triphosphine.

[0039] By introducing boron or phosphorus as doping elements, the conductivity of the carbon substrate is significantly improved. The p-type impurities introduced by boron doping can increase the carrier concentration, and phosphorus doping as an n-type impurity can improve the electron mobility. Both can improve the overall conductivity of the negative electrode material and meet the needs of high-rate charging and discharging. Non-metallic doping can introduce more active sites in the carbon substrate, promote the embedding and de-embedding process of lithium ions, and improve the specific capacity and energy density of the negative electrode material. Boron or phosphorus doping enhances the interfacial bonding between the carbon substrate and silicon particles, reduces the structural damage caused by silicon volume changes during charging and discharging, and extends the cycle life of the battery.

[0040] Through plasma enhanced chemical vapor deposition, non-metallic doping gases are efficiently activated, and the generated active species can penetrate deep into the porous structure, achieving uniform and efficient doping distribution and ensuring the consistency of material performance. By precisely controlling the flow rate and plasma power of non-metallic doping gases, precise adjustment of doping concentration and distribution can be achieved to meet the specific requirements of negative electrode material performance in different application scenarios.

[0041] S2.3, stop introducing non-metallic doping gas, introduce silane gas, the silane gas flow rate is controlled at 0.5-10 L / min, the reaction temperature is 500-700°C, the plasma power is 200-500 W, and the doping time is 100-1500 min. The silane gas includes at least one of monosilane, disilane, and silane derivatives.

[0042] By introducing silicon, the theoretical specific capacity of the negative electrode material is greatly improved (the theoretical capacity of silicon is about 4200mAh / g, far exceeding the approximately 372mAh / g of graphite), significantly improving the energy density of the battery. Silane gas is activated by plasma to form nano-scale silicon particles or films, which are evenly distributed in the pores of the porous carbon substrate. This uniform distribution ensures that the silicon particles can be efficiently utilized during the charge and discharge process, avoiding structural damage caused by local excessive expansion.

[0043] A strong interface bond is formed between silicon particles and the carbon substrate, and the high-energy species in the plasma deposition process promote the formation of chemical bonds between carbon and silicon, enhance the overall structural stability of the material, and reduce capacity decay during the cycle. The high specific surface area and good conductivity of silicon nanoparticles make the embedding and de-embedding process of lithium ions more efficient, improve the rate performance of negative electrode materials, and meet the needs of high-power applications.

[0044] S2.4. Stop introducing silane gas, introduce an inert atmosphere, slowly lower the temperature to room temperature, and control the cooling rate at 5 to 20°C / min to obtain a non-metal-doped silicon-based material.

[0045] By controlling the cooling rate at 5-20°C / min, thermal stress and structural defects (such as cracks and pore collapse) caused by rapid cooling of the material can be avoided, and the overall structural integrity and pore morphology of the material can be maintained. The slow cooling process helps to stabilize the distribution of doped non-metallic elements and deposited silicon particles in the porous carbon substrate, ensure the firm interface between the silicon and carbon substrates, and improve the mechanical and electrochemical stability of the material. Slow cooling helps to maintain the microstructure of nano-scale silicon particles and carbon layers, prevent silicon particles from aggregating or growing due to thermal stress, and ensure that the negative electrode material has a high specific surface area and high conductivity. Slow cooling in an inert atmosphere prevents the material from reacting with oxygen in the air during the cooling process, maintains the purity of non-metallic doping and silicon deposition, and ensures the high performance and long life of the material.

[0046] S3, performing multi-layer carbon coating on the surface of the silicon-based material to obtain a silicon-based negative electrode precursor; S3.1. A mixed gas of acetylene and hydrogen is introduced into a plasma vapor deposition reactor to carry out the first deposition reaction. The gas flow rate of acetylene is 5-10 L / min, the gas flow rate of hydrogen is 10-20 L / min, the reaction temperature is 500-800°C, the deposition time is 30-120 min, and the plasma power is 300-600 W to form a first carbon coating layer on the silicon-based material.

[0047] The role of the first layer of carbon coating: through the reaction of acetylene and hydrogen mixed gas, the generated carbon coating layer (mainly graphene or graphite-like structure) forms a solid interface on the surface of the silicon-based material. This layer of carbon material provides a good conductive network for the subsequent silicon-based negative electrode material, improves the overall conductivity, and ensures the electron transmission efficiency of silicon particles.

[0048] The first layer of carbon coating formed on the surface of the silicon-based material plays a role in buffering the volume expansion of silicon. Silicon undergoes a large volume change during the charge and discharge process, and the carbon coating can effectively slow down this change, reduce the cracking and shedding of the material, and thus improve the cycle stability of the material.

[0049] The carbon structure of the coating helps to increase the transfer rate of lithium ions, especially during high-rate charge and discharge. The high conductivity of this layer of carbon allows lithium ions to be quickly embedded and de-embedded, increasing the power density and charging rate of the negative electrode material.

[0050] The first deposited carbon layer usually has a certain pore structure, which helps to increase the specific surface area of ​​the material and provide additional space for the storage of lithium ions, further improving the specific capacity of the material.

[0051] S3.2. Stop introducing the mixed gas of acetylene and hydrogen, and introduce a mixed gas of ethylene or methane gas and nitrogen or argon gas to carry out a second deposition reaction. The gas flow rate of ethylene or methane is 2~6L / min, the gas flow rate of nitrogen or argon is 8~12L / min, the reaction temperature is 700~900℃, the deposition time is 20~80min, and the plasma power is 300~600W. A second carbon coating layer is formed on the first carbon coating layer to obtain a silicon-based negative electrode precursor.

[0052] The thickness of the first carbon coating layer is 5-15 nm, and the thickness of the second carbon coating layer is 3-10 nm; by volume ratio, acetylene: hydrogen = 1:2, ethylene or methane: nitrogen or argon = 1:3.

[0053] During the deposition process of step S3, in order to accurately control the dynamic changes of temperature and plasma power during the reaction process, it is ensured that the best doping effect is achieved in different deposition stages.

[0054] The following are the governing equations based on temperature and power regulation during the reaction process.

[0055] in, is the temperature in the reactor (°C), P(t) is the plasma power (W), k is the heat transfer coefficient, which indicates the heat loss rate (W / °C), is the ambient temperature (°C), assumed to be room temperature, C is the heat capacity of the plasma vapor deposition reactor (J / °C), which depends on the material and volume of the reactor, is the initial plasma power (W), is the maximum plasma power (W), is the maximum deposition time (min), To control the exponential, adjust the speed at which the power increases, with a value between 0.5 and 2. This parameter controls the curve shape of the power growth. For example, =1, the power increases linearly with time; When >1, the power increases faster.

[0056] For the deposition of multiple carbon coating layers, a fluidized bed chemical vapor deposition reactor can also be used. The carrier gas is introduced through the gas delivery system, and the gas flow rate is adjusted to ensure that the powder is fluidized in the reactor. The gas flow rate should be controlled in an appropriate range so that the powder particles can be suspended and fully contacted. The heating system is started to increase the reactor temperature to the desired deposition temperature. Temperature control is key to ensure that the reaction gas decomposes and deposits on the powder surface.

[0057] S4. Heat-treating the silicon-based negative electrode precursor to obtain a non-metal-doped silicon-based negative electrode material.

[0058] Step S4 includes: S4.1. Set the heating rate to 5-10°C / min until the temperature of the silicon-based negative electrode precursor reaches 800-1000°C, and the insulation time is 120-240min.

[0059] The heating process in this step can cause a high-temperature reaction between the multi-layer carbon coating and the silicon-based material, promoting the structural solidification of the silicon-based negative electrode. By precisely controlling the heating rate and the holding time, the silicon particles and the carbon coating become more tightly bonded, forming a more stable structure. This helps to improve the material's cycle stability and prevent the silicon material from cracking or peeling off due to expansion during the charge and discharge process.

[0060] During the heating process, non-metallic dopants (such as boron or phosphorus) can react with silicon-based materials in a solid state, ensuring that the doping elements are evenly distributed inside the silicon-based materials, thereby improving their electrochemical performance. This process optimizes the combination of doping elements with silicon, enhances the conductivity and ion migration rate of the material, and improves the overall performance of the battery.

[0061] Through this heating process, the interface bonding between the formed carbon layer and the silicon-based material is further enhanced. This high-temperature treatment makes the conductive network of the carbon coating layer more perfect, and the structure of the carbon material tends to be highly conductive graphene or graphite-like phase structure, further improving the electronic conductivity of the silicon-based negative electrode and providing a guarantee for high-power applications.

[0062] During the heat preservation process, the pore structure of silicon-based negative electrode materials is further optimized. The expansion and contraction of silicon is alleviated at high temperatures. At the same time, the pore structure will be refined and strengthened during the heating and heat preservation process, which helps to increase the specific surface area of ​​the material and provide more lithium ion embedding and de-embedding sites, thereby improving the specific capacity and cycle performance of the material.

[0063] S4.2. Introduce ammonia or nitrogen gas with a gas flow rate of 5 to 15 L / min, adjust the heating rate to 2 to 5°C / min, until the temperature of the silicon-based negative electrode precursor reaches 1000 to 1200°C, and keep warm for 120 to 240 minutes to obtain a non-metal-doped silicon-based negative electrode material.

[0064] In this step, the introduction of ammonia or nitrogen gas helps to further uniformly incorporate non-metallic doping elements (such as boron, phosphorus, etc.) into the silicon-based material at high temperature. These doping elements can effectively form chemical bonds with silicon or carbon, improve the structural stability, conductivity and compatibility of the negative electrode material with the electrolyte. This doping helps to improve the cycle performance and rate performance of the material, especially under high temperature conditions.

[0065] The effect of ammonia or nitrogen gas at high temperature can inhibit the crystal structure degradation of silicon particles and maintain the good lattice structure of silicon materials. By stabilizing the silicon particles, the cracking of silicon particles due to excessive volume expansion and contraction during the charge and discharge process can be avoided, thereby improving the long-term cycle performance of the negative electrode material.

[0066] Ammonia, as a nitrogen source gas, can introduce nitrogen into silicon-based materials. Nitrogen doping can increase the conductivity of silicon materials and improve the efficiency of lithium ion insertion and extraction. In addition, the incorporation of nitrogen can also effectively optimize the electrochemical window of the material, reduce the capacity attenuation caused by side reactions during long-term use of the battery, and further improve the rate performance and cycle stability of the material.

[0067] In the environment of ammonia or nitrogen gas, high temperature heat treatment can further optimize the porous structure of silicon-based negative electrode. The presence of nitrogen and ammonia helps to form micropores or mesopores on the surface of the material. These pores can provide more space for the embedding of lithium ions, improve the storage capacity and transmission rate of lithium ions, and enhance the specific capacity and high rate performance of negative electrode materials.

[0068] The introduction of ammonia or nitrogen gas can effectively inhibit the occurrence of side reactions in the battery, especially at high temperatures, it can reduce the reaction between the material and the electrolyte and improve the chemical stability of the material. In this way, the surface protective layer of the material is more stable, which can effectively prevent the rapid degradation of the material and increase the service life of the battery.

[0069] Example 1: 3000g of porous carbon with a hierarchical pore structure was added to a PECVD furnace, and nitrogen was introduced at a flow rate of 5L / min for 60min. The temperature in the PECVD furnace was raised to 520°C, and diborane gas was introduced at a flow rate of 1L / min for 300min to obtain a boron-doped porous carbon substrate. The temperature in the furnace was then raised to 600°C, and monosilane was introduced at a flow rate of 5L / min for 500min to obtain a boron-doped silicon-based material. A mixed gas of acetylene and hydrogen was introduced, with a gas flow rate of 5L / min for acetylene and a gas flow rate of 10L / min for hydrogen, for 100min, and a mixed gas of ethylene and nitrogen was introduced, with a gas flow rate of 2L / min for ethylene and a gas flow rate of 8L / min for nitrogen, for 50min. After heat treatment, a boron-doped silicon-based negative electrode material coated with a carbon layer was obtained.

[0070] Example 2: 3000g of porous carbon with a hierarchical pore structure was added to the PECVD furnace, and nitrogen was introduced at a flow rate of 5L / min for 60min. The temperature in the PECVD furnace was raised to 600°C, and diborane gas was introduced at a flow rate of 2L / min for 150min to obtain a boron-doped porous carbon substrate. The temperature in the furnace was then raised to 650°C, and monosilane was introduced at a flow rate of 10L / min for 500min to obtain a boron-doped silicon-based material. A mixed gas of acetylene and hydrogen was introduced, with a gas flow rate of 10L / min for acetylene and a gas flow rate of 20L / min for hydrogen, for 80min, and a mixed gas of methane and argon was introduced, with a gas flow rate of 5L / min for methane and a gas flow rate of 5L / min for argon, for 80min. After heat treatment, a boron-doped silicon-based negative electrode material coated with a carbon layer was obtained.

[0071] Example 3: 3000g of porous carbon with a hierarchical pore structure was added to the PECVD furnace, and nitrogen was introduced at a flow rate of 5L / min for 60min. The temperature in the PECVD furnace was raised to 520°C, and phosphine gas was introduced at a flow rate of 1L / min for 300min to obtain a phosphorus-doped porous carbon substrate. The temperature in the furnace was then raised to 600°C, and monosilane was introduced at a flow rate of 5L / min for 500min to obtain a phosphorus-doped silicon-based material. A mixed gas of acetylene and hydrogen was introduced, with a gas flow rate of 5L / min for acetylene and a gas flow rate of 10L / min for hydrogen, for 100min, and a mixed gas of ethylene and nitrogen was introduced, with a gas flow rate of 2L / min for ethylene and a gas flow rate of 8L / min for nitrogen, for 50min. After heat treatment, a phosphorus-doped silicon-based negative electrode material coated with a carbon layer was obtained.

[0072] Example 4: 3000g of porous carbon was added to the PECVD furnace, and nitrogen was introduced at a flow rate of 5L / min for 60min. The temperature in the PECVD furnace was raised to 600°C, and phosphine gas was introduced at a flow rate of 2L / min for 150min to obtain a phosphorus-doped porous carbon substrate. The temperature in the furnace was then raised to 650°C, and monosilane was introduced at a flow rate of 10L / min for 500min to obtain a phosphorus-doped porous silicon-carbon material. A mixed gas of acetylene and hydrogen was introduced, with a gas flow rate of 10L / min for acetylene and a gas flow rate of 20L / min for hydrogen, for 80min, and a mixed gas of methane and argon was introduced, with a gas flow rate of 5L / min for methane and a gas flow rate of 5L / min for argon, for 80min. After heat treatment, a coated carbon layer was obtained.

[0073] Figure 2The upper left corner (SEM image) shows the surface morphology of the boron-doped silicon-based anode material, and the particle morphology of the material can be seen. The surface is smooth and uniform, suitable for further analysis of its element distribution.

[0074] Figure 2 Upper right corner (Si element distribution map): The distribution map of silicon element (Si) in the material through X-ray energy spectrum analysis (EDS). This shows that the silicon element is evenly distributed in the material. As the main component of the negative electrode material, silicon plays an important role in silicon-based negative electrode materials.

[0075] Figure 2 Lower left corner (C element distribution diagram): shows the distribution of carbon element (C). Since silicon-based materials usually have a carbon coating layer, the distribution diagram of carbon here can show whether the carbon coating layer is evenly covered on the surface of silicon particles.

[0076] Figure 2 Lower right corner (B element distribution diagram): shows the distribution of boron (B) in the material. Boron is evenly distributed on the surface of silicon particles, proving that boron has been successfully doped into silicon-based negative electrode materials.

[0077] This figure shows that through appropriate processes, boron elements have been successfully doped into silicon-based negative electrode materials, and the carbon coating layer is evenly covered, which can improve the conductivity and stability of the material.

[0078] Figure 3 Upper left corner (SEM image): shows the surface morphology of the phosphorus-doped silicon-based negative electrode material. It can be seen that the appearance of its particles may be different from that of the boron-doped material, and there may be different structural features on the surface.

[0079] Figure 3 Upper right corner (Si element distribution diagram): shows the distribution of silicon element (Si), indicating that silicon is also the main component of this material and is evenly distributed.

[0080] Figure 3 Lower left corner (C element distribution map): shows the distribution of carbon element (C). As with the boron-doped samples, a carbon coating may exist to ensure that the silicon particles are not oxidized.

[0081] Figure 3 Lower right corner (P element distribution diagram): shows the distribution of phosphorus (P). The phosphorus element is evenly distributed, indicating that the phosphorus element has been successfully doped into the silicon-based negative electrode material.

[0082] Phosphorus-doped silicon-based negative electrode materials also have uniform doping and carbon coating layers. The phosphorus element can enhance the cycle stability and conductivity of the material.

[0083] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a non-metal-doped silicon-based negative electrode material, characterized in that: The following steps are involved: S1. Preparing a porous carbon substrate with a hierarchical pore structure, wherein the pore size of the porous carbon substrate is 0.1-100 nm, and the hierarchical pore structure includes 30-90% micropores, 5-55% mesopores and 5-55% macropores in percentage, the pore size of the micropores is 0.1-2 nm, the pore size of the mesopores is 2-50 nm, and the pore size of the macropores is 50-100 nm; S2, sequentially depositing a non-metallic doping gas and a silane gas in the porous carbon substrate to obtain a non-metallic doped silicon-based material, wherein the non-metallic doping gas comprises a borane gas or a phosphine gas; S3, performing multi-layer carbon coating on the surface of the silicon-based material to obtain a silicon-based negative electrode precursor; S4. Heat-treating the silicon-based negative electrode precursor to obtain a non-metal-doped silicon-based negative electrode material.

2. The method for preparing a non-metal-doped silicon-based negative electrode material according to claim 1, characterized in that: The step S1 comprises: S1.

1. Clean, dry and crush the carbon source material to obtain a uniform particle size distribution, and the particle size D50 value is controlled at 5 to 10 μm; S1.2, adding a template material to the carbon source material, the mass ratio of the carbon source material to the template material is controlled at 1:2, heating to 800-1000°C, a heating rate of 5-10°C / min, and a holding time of 2-4h to obtain a premix; S1.3, transferring the premix to a hydrofluoric acid solution to remove the template material, controlling the temperature at room temperature, and reacting for 4 to 6 hours to obtain a porous carbon substrate with a hierarchical pore structure.

3. The method for preparing a non-metal-doped silicon-based negative electrode material according to claim 2, characterized in that: In the step S1, the carbon source material includes at least one of porous carbon, natural graphite, artificial graphite mesophase carbon microbeads, and expanded graphite; The pore size of the porous carbon substrate is 0.1-100 nm, wherein, calculated by percentage, the hierarchical pore structure includes 30-90% of micropores, 5-55% of mesopores and 5-55% of macropores.

4. The method for preparing a non-metal-doped silicon-based negative electrode material according to claim 2, characterized in that: After step S1.3, step S1 further includes: S1.4, immersing the porous carbon substrate in potassium hydroxide or phosphoric acid solution, the proportion of which is controlled to be 2-10% of the mass of the carbon source, immersing for 1-4 hours, and calcining at 500-700° C. for 2-4 hours; S1.5, transferring the porous carbon substrate to a strong oxidant solution, controlling the temperature at 60-100°C, and reacting for 2-6 hours; S1.

6. Use deionized water to wash repeatedly to remove unreacted products. The drying temperature is 100-150°C for 4-6 hours to obtain a porous carbon substrate with a hierarchical pore structure after activation.

5. The method for preparing a non-metal-doped silicon-based negative electrode material according to claim 1, characterized in that: The step S2 comprises: S2.1, placing the porous carbon substrate in a plasma vapor deposition reactor under an inert atmosphere, with an inert gas flow rate of 1-20 L / min, preheating to 400-700°C, and maintaining for 40-100 min to remove impurities and moisture adsorbed on the surface; S2.2, stop introducing the inert gas, introduce the non-metallic doping gas, the flow rate of the non-metallic doping gas is controlled at 0.5-10 L / min, the reaction temperature is 400-600°C, the plasma power is 200-500 W, and the doping time is 30-420 min; S2.3, stop introducing non-metallic doping gas, introduce silane gas, the silane gas flow rate is controlled at 0.5-10L / min, the reaction temperature is 500-700°C, the plasma power is 200-500W, and the doping time is 100-1500min; S2.

4. Stop introducing silane gas, introduce an inert atmosphere, slowly lower the temperature to room temperature, and control the cooling rate at 5 to 20°C / min to obtain a non-metal-doped silicon-based material.

6. The method for preparing a non-metal-doped silicon-based negative electrode material according to claim 5, characterized in that: In step S2, The inert gas includes at least one of nitrogen, argon and hydrogen; The borane gas includes at least one of diborane, methylborane, tetraborane, pentaborane, decaborane, hexaborane and trimethylborane; The phosphine gas includes at least one of phosphine, diphosphine and triphosphine; The silane gas includes at least one of monosilane, disilane, and silane derivatives.

7. The method for preparing a non-metal-doped silicon-based negative electrode material according to claim 1, characterized in that: The step S3 comprises: S3.1, introducing a mixed gas of acetylene and hydrogen into a plasma vapor deposition reactor to perform a first deposition reaction, wherein the gas flow rate of acetylene is 5-10 L / min, the gas flow rate of hydrogen is 10-20 L / min, the reaction temperature is 500-800° C., the deposition time is 30-120 min, and the plasma power is 300-600 W to form a first carbon coating layer on the silicon-based material; S3.

2. Stop introducing the mixed gas of acetylene and hydrogen, and introduce a mixed gas of ethylene or methane gas and nitrogen or argon gas to carry out a second deposition reaction. The gas flow rate of ethylene or methane is 2~6L / min, the gas flow rate of nitrogen or argon is 8~12L / min, the reaction temperature is 700~900℃, the deposition time is 20~80min, and the plasma power is 300~600W. A second carbon coating layer is formed on the first carbon coating layer to obtain a silicon-based negative electrode precursor.

8. The method for preparing a non-metal-doped silicon-based negative electrode material according to claim 7, characterized in that: The thickness of the first carbon coating layer is 5-15 nm, and the thickness of the second carbon coating layer is 3-10 nm; By volume ratio, acetylene: hydrogen = 1:2, ethylene or methane: nitrogen or argon = 1:

3.

9. The method for preparing a non-metal-doped silicon-based negative electrode material according to claim 1, characterized in that: The step S4 comprises: S4.1, setting the heating rate to 5-10°C / min, until the temperature of the silicon-based negative electrode precursor reaches 800-1000°C, and the holding time is 120-240min; S4.

2. Introduce ammonia or nitrogen gas with a gas flow rate of 5 to 15 L / min, adjust the heating rate to 2 to 5°C / min, until the temperature of the silicon-based negative electrode precursor reaches 1000 to 1200°C, and keep warm for 120 to 240 minutes to obtain a non-metal-doped silicon-based negative electrode material.

Citation Information

Patent Citations

  • Silicon-based negative electrode material, preparation method thereof and lithium ion battery containing silicon-based negative electrode material

    CN115050950A

  • Silicon-carbon negative electrode material and preparation method and application thereof

    CN115966684A

  • Phosphorus-silicon co-doped silicon-carbon composite negative electrode material and preparation method thereof

    CN118954517A

  • System and method for preparing silicon-carbon negative electrode of circulating fluidized bed

    CN119034624A

Cited By

  • System and process method capable of continuously preparing high-gram-volume and low-expansion silicon-carbon material

    CN120054376A

  • Silicon-carbon composite material as well as preparation method and application thereof

    CN121023470A

  • Silicon-carbon composite material, preparation method and application thereof

    CN121023470B